2017
DOI: 10.1093/ajae/aax074
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation and Productivity: Empirical Evidence on Dairy Production

Abstract: We investigate productivity development and its relation to resource reallocation effects in the dairy sector in southeast Germany during the phasing-out of the European Union milk quota. We use a farm level dataset containing financial accounting data for a period of 15 years. Farm-level productivity is estimated by applying a proxy approach recently introduced in the literature. We compare this approach to other estimation approaches as well as an index based analysis. After aggregation we decompose sector p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
2
40
1
1
Order By: Relevance
“…In detail, it can be concluded that the main source of dairy productivity growth in most regions of the EU was the increasing size of specialized dairy farms, accompanied by structural changes associated with the concentration of production in the most competitive regions. The changes were amplified by the release and subsequent abolition of milk quotas, which prevented the increase in output and reallocation of inputs among producers and thereby produced welfare losses (see Kumbhakar et al, 2008 andFrick andSauer, 2016).…”
Section: Productivity Of Czech Milk Production In European Comparisonmentioning
confidence: 99%
“…In detail, it can be concluded that the main source of dairy productivity growth in most regions of the EU was the increasing size of specialized dairy farms, accompanied by structural changes associated with the concentration of production in the most competitive regions. The changes were amplified by the release and subsequent abolition of milk quotas, which prevented the increase in output and reallocation of inputs among producers and thereby produced welfare losses (see Kumbhakar et al, 2008 andFrick andSauer, 2016).…”
Section: Productivity Of Czech Milk Production In European Comparisonmentioning
confidence: 99%
“…A particularly large number of studies focus on milk quotas or other market regulations, starting from an assessment of the milk quota system (e.g., [18,19]) or of its operational impacts on the performance of dairy farms (e.g., [20][21][22]), through to comparative analyses of agricultural policies for the milk market (e.g., [2]), studies on how the farmers respond to political and market change (e.g., [23]), and research on the impact of the abolition of milk quotas on the functioning of dairy farms (e.g., [24][25][26]). Often, research projects focus on the situation prevailing in selected countries, as it is the case in [18][19][20][21][23][24][25][26]. Selected countries are also addressed by analyses of the economic situation [27] and competitiveness [28] of dairy farms, or of the strategy of households in that sector [29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the dairy industry manages production according to high quantitative and qualitative criteria, placing modern dairy farming within a highly competitive national and international supply chain. However, dairy farms have been exposed to wide variation in profit levels due to considerable variability of milk price, and energy and feed costs [1][2][3][4] . For these reasons, it is necessary that the dairy industry improves competitiveness by adopting innovative production processes and improving animal welfare.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic assessment of milk composition is useful for several reasons: (1) to differentiate animals producing low-or high-quality milk [16] , (2) to monitor animal health status [17][18][19] , and (3) to perform a real-time separation. In particular, the separation of milk may be a useful way to obtain two products with different quality characteristics, such as nutraceutical cheese-making properties, from the same dairy farm.…”
Section: Introductionmentioning
confidence: 99%